The effect of residual antibiotics in food on intestinal microbiota: a systematic review - Sadighara, Parisa; Rostami, Shahrbano; Shafaroodi, Hamed; Sarshogi, Ali; Mazaheri, Yeghaneh; Sadighara, Melina (Frontiers in Sustainable Food Systems, 2023)
Introduction The gut microbiota may be altered following changes in diet or exposure to drugs. Humans can be exposed to antibiotic residue in food. People may be exposed to these compounds for years. But in determining the maximum residue level (MRL), the effects of antibiotic residue on the intestinal microbiota are not investigated. Some evidence suggests that antibiotics in small amounts also lead to changes in the intestinal microbiota. Therefore, a systematic study was conducted with the aim of investigating the effect of antibiotic residues in food on the intestinal microbiota. Method The main criterion of this research was to investigate the effects of antibiotics at low doses. For this purpose, a search was made in the databases with keywords antibiotic, veterinary antibiotic, food, residue, microbiome, and microbiota. The investigated doses of each of the antibiotics in the studies were compared with their MRL in food. Results The most significant change in the structure and function of the microbiota was made by tetracycline, sulfamethoxazole, cefquinome, florfenicol and tylosin. The lowest observed effect was related to the antibiotics fosfomycin and amoxicillin. Discussion Exposure to antibiotic residues through food is usually a long-term exposure. In vivo studies, changes in the intestinal microbiota were observed. Therefore, it is necessary to inform the breeders and competent authorities in order to comply with the principles of treatment. The gut microbiota may be altered following changes in diet or exposure to drugs.